The Effect of Intellectual Capital on the Profitability of the Banking Companies Listed on Indonesia Stock Exchange in 2013-2016 - Silvia, Lely; Maftukhah, Ida (Management Analysis Journal, 2018)
The purpose of this study is to know the effect of intellectual capital to profitability of banking companies. The sample of this research is 35 banking companies listed in Indonesia Stock Exchange 2013-2016. The method of data analysis using multiple regression analysis. The result showed the regression coefficients variable VACA is as much as 2.632 and sig score 0.010; regression coefficient variable is as much as 4.256 and sig score 0.000; regression coefficient variable is as much as -1.148 and sig score 0.253. The concusion of this research is VACA and VAHU have positif dan significant effect on profitability of banking companies, and STVA has negative and no significant effect on profitability of banking companies.